LAS POLÍTICAS PÚBLICAS COMO PERSPECTIVA DE ANÁLISIS - Abarca Rodríguez, Allan (2023)
There was a notable increase in professional research dealing with public problems and their resolution in the 1990s, made evident by an academic shift: researches stopped asking about the size or competence of Government and began inquiring about how to deal with public affairs. “Public policy” analyses and analyses “for public policy” offer a two-fold approach: they present a new method for understanding the interaction between government institutions, NGOs, the private sector, and citizens; and they provide the necessary tools to solve both specific and general problems.